Single‐cell biology: what does the future hold? - Maria Polychronidou; Jingyi Hou; M Madan Babu; Prisca Liberali; Ido Amit; Bart Deplancke; Galit Lahav; Shalev Itzkovitz; Matthias Mann; Julio Saez‐Rodriguez; Fabian Theis; Roland Eils (Molecular Systems Biology)
Graphical Abstract In this Editorial, our Chief Editor and members of our Advisory Editorial Board discuss recent breakthroughs, current challenges, and emerging opportunities in single‐cell biology and share their vision of “where the field is headed.”